Some results of a random $(b, θ)$-Enriched contraction with application on non-linear stochastic integral equations - Krissada Yajai; Orapan Janngam; Wiroj Mongkolthep; Phachara Saipara (Statistics, Optimization & Information Computing, 2025)
In this paper, we propose a random $(b, θ)$-enriched contraction operator and prove an existence theorem of random fixed points for this operator. Moreover, we establish an existence result for a solution to a nonlinear stochastic integral equation of Hammerstein type.